Evaluation of Vitamin D Levels in Patients Treated in Physical Medicine and Rehabilitation Service - Esra Şahingöz Bakırcı; Gülseren Demir Karakılıç; Ferda Büyük (Galenos Yayinevi, 2023)
Objective: The background of our study is to detect the frequency of vitamin D deficiency in hospitalized patients who had been administered physical medicine and rehabilitation (PMR) programs and the distribution of vitamin D deficiency according to patient groups. Materials and Methods: A total of 1210 patients (805 females and 405 males) who received a PMR program in the inpatient clinics of a secondary state hospital between 01.01.2017 and 01.08.2022 were retrospectively included in the study. Age, gender, hospitalization diagnosis, serum 25-hydroxyvitamin D [25(OH)D] values were recorded. Results: The median age of the participants was 64 (54-72). The median 25(OH)D value was 13.16 (8.73-19.36). When the participants were categorized into groups considering the diagnoses for which they were applied the physical therapy program, and 25(OH)D values were compared, a meaningful difference was determined between the diagnosis groups (p=0.020). The lowest median value was found in the group with internal derangement of the knee, muscle, and tendon injury group, followed by the neurologic rehabilitation group. The highest median 25(OH)D level was determined in the orthopedic rehabilitation group. Vitamin D deficiency or insufficiency was found in 93,9% of the patients. The neurologic rehabilitation group had the highest severe deficiency ratio (38.1%). Conclusion: Vitamin D deficiency is often seen in patients hospitalized in PMR services. Therefore, we think measuring vitamin D levels during hospitalization and providing replacement and maintenance treatments if deficiency is detected may improve rehabilitation outcomes.